TMT-Based Quantitative Proteomic Analysis Reveals the Physiological Regulatory Networks of Embryo Dehydration Protection in Lotus (Nelumbo nucifera) - Zhang, Di; Liu, Tao; Sheng, Jiangyuan; Lv, Shan; Ren, Li (Frontiers in Plant Science, 2021)
Lotus is an aquatic plant that is sensitive to water loss, but its seeds are longevous after seed embryo dehydration and maturation. The great difference between the responses of vegetative organs and seeds to dehydration is related to the special protective mechanism in embryos. In this study, tandem mass tags (TMT)-labeled proteomics and parallel reaction monitoring (PRM) technologies were used to obtain novel insights into the physiological regulatory networks during lotus seed dehydration process. Totally, 60,266 secondary spectra and 32,093 unique peptides were detected. A total of 5,477 proteins and 815 differentially expressed proteins (DEPs) were identified based on TMT data; of these, 582 DEPs were continuously down-regulated and 228 proteins were significantly up-regulated during the whole dehydration process. Bioinformatics and protein-protein interaction network analyses indicated that carbohydrate metabolism (including glycolysis/gluconeogenesis, galactose, starch and sucrose metabolism, pentose phosphate pathway, and cell wall organization), protein processing in ER, DNA repair, and antioxidative events had positive responses to lotus embryo dehydration. On the contrary, energy metabolism (metabolic pathway, photosynthesis, pyruvate metabolism, fatty acid biosynthesis) and secondary metabolism (terpenoid backbone, steroid, flavonoid biosynthesis) gradually become static status during lotus embryo water loss and maturation. Furthermore, non-enzymatic antioxidants and pentose phosphate pathway play major roles in antioxidant protection during dehydration process in lotus embryo; abscisic acid (ABA) signaling and the accumulation of oligosaccharides, late embryogenesis abundant proteins, and heat shock proteins may be the key factors to ensure the continuous dehydration and storage tolerance of lotus seed embryo. Stress physiology detection showed that H2O2 was the main reactive oxygen species (ROS) component inducing oxidative stress damage, and glutathione and vitamin E acted as the major antioxidant to maintain the REDOX balance of lotus embryo during the dehydration process. These results provide new insights to reveal the physiological regulatory networks of the protective mechanism of embryo dehydration in lotus.